2015
DOI: 10.1039/c4ob02646b
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of telomeric i-motif stability by 5-methylcytosine and 5-hydroxymethylcytosine modification

Abstract: The two important epigenetic markers in the human genome, 5-methylcytosine (mC) and 5-hydroxymethylcytosine (hmC), are involved in gene regulation processes. As a major epigenetic target, cytosines in a C-rich DNA sequence were substituted with mC and hmC to investigate the thermal stability and pH sensitivity of the corresponding i-motifs. Circular Dichroism (CD) studies indicate the formation of i-motifs at acidic pH (<6.5) for mC- and hmC-modified DNA sequences. Thermal denaturation results suggest that DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 46 publications
4
56
1
Order By: Relevance
“…Whereas psC located at the ends of the C-stack stabilizes the i-motif, substitutions in central position provoke the opposite effect. This destabilization is similar to that found for 5-hydroxymehtylcystosine 22 or UNA 33 , and not as pronounced as other destabilizing modifications like acyclic threoninol derivatives 34 .…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Whereas psC located at the ends of the C-stack stabilizes the i-motif, substitutions in central position provoke the opposite effect. This destabilization is similar to that found for 5-hydroxymehtylcystosine 22 or UNA 33 , and not as pronounced as other destabilizing modifications like acyclic threoninol derivatives 34 .…”
Section: Resultssupporting
confidence: 80%
“…The stabilization observed for CC9 is not as high as that observed for 2′-F-araC substitutions 25 , but comparable with the effect of 5-methylcytosines 22 , LNA 23 and other stabilizing sugar substitutions 31 . As in the case of LNA 32 , the effect of psC substitutions on the overall pH T is highly dependent on their particular position.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Some stabilization of the i‐motif at neutral pH was observed, but these results were obtained for short tetrameric structures and are difficult to extrapolate to biologically relevant intramolecular i‐motifs. As cytidine is subject to epigenetic modifications, the presence of 5‐methyl‐C and 5‐hydroxymethyl‐C in the C‐rich telomere sequence has been studied, thus showing small changes in the stability of the modified i‐motifs . Interestingly, it has been observed that the inclusion of ribocytidines destabilizes i‐motifs, but arabino‐cytidines have the opposite effect .…”
Section: Discussionmentioning
confidence: 99%
“…Base modifications such as 5‐methylcytosine and 5‐hydroxymethylcytosine are permissive bases that can be adapted to i‐motif structures. They show position‐dependent stability and different behavior under experimental crowding conditions . These bases are important epigenetic markers in the human genome.…”
Section: Introductionmentioning
confidence: 99%